OCP Oracle Certified Professional Java SE 17 Developer (Exam 1Z0-829) programmer's guide - Mughal, Khalid A.; Strelnikov, Vasily A. (Rough cuts., 2023)
OCP Oracle Certified Professional Java SE 17 Developer Exam 1Z0-829 Programmer's Guide is a unique guide that combines a rigorous introduction to programming in Java with meticulous coverage of the Java SE 17 and Java SE 11 Developer exam objectives. Fully updated to reflect changes in the latest exams, it features increased focus on analyzing code scenarios--not just individual language constructs. Each objective is thoroughly addressed, reflecting the latest features and APIs, as well as best practices for taking the exam. The one book anyone studying for Java SE 17 Developer or Java SE 11 Developer certification needs, it features Easy to find coverage of key topics relevant to each exam objective An introduction to essential concepts in object-oriented programming (OOP) and functional-style programming In-depth coverage of declarations, access control, operators, flow control, OOP techniques, lambda expressions, streams, modules, concurrency, Java I/O, key API classes and much more Program output demonstrating expected results from complete Java programs Unique diagrams to illustrate important concepts, such as Java I/O, modules, and streams Extensive use of UML (Unified Modeling Language) to illustrate program design Dozens of review questions with annotated answers to help prepare for the exam and a complete Mock Exam.